Locus de controle, comprometimento organizacional e satisfação no trabalho: um estudo correlacional - Xavier, Valéria Melo Claudino (2005)
The present study looked for to verify the relationship among the variables locus of control, organizational commitment and job satisfaction. The research was accomplished with 202 subjects, employed professionals in organizations, and that you/they were studying graduation in administration in an university peculiar of the city of Uberlândia. It was used in the study a theoretical model formed by two groups of variables, having been these measured through a specific instrument. They are them - biographical and professional variables, that you/they include sex, age, marital status, school formation, professional experience, section of performance, time of company, wage and formal socialization; and organizational variables: expectation level assisted in the first months of work, number of courses accomplished by the company, number of received promotions and evaluation of the training offer as development opportunity. The variables were: organizational commitment (affectionate, normative and instrumental) and job satisfaction (with the work friends, with the leadership, with the wage, with the promotions and with the nature of the work). The variable organizational commitment was based on the studies of the three dimensions of Meyer, Allen; Smith (1993), and the scale adapted in Brazil by Medeiros (1997). Already the variable job satisfaction was measured through a scale maid and validated by Siqueira (1995). The third construto involved in the study, locus of control, a personal variable was considered, partially defined for the biographical and professional variables. This variable was measured through the scale "locus of control in the work" proposed by Spector (1988) and validated for the brazilian context by Bastos (1991). The results demonstrate to prevail in the sample the affectionate bond of the commitment, as well as larger satisfaction with the work friends. In relation to the variable locus of control the larger tendency is verified to the locus of internal control. He/she still stands out, the existence of relationships between the commitment types and the two dimensions of the locus.